Implementation of accounting in the system of integrated business structures - Kosata, Inna (Technology audit and production reserves, 2019)
The object of research is the European integration of Ukrainian accounting. One of the most problematic places is the insufficient compliance of Ukrainian accounting with international standards, which prevents Ukraine from integrating into the global financial space. Empirical research methods (observation, comparison, generalization), theoretical research methods and the analytical method are used. The paper discusses in detail the differences between the Provision (standard) of accounting of Ukraine and the International standards of financial reporting and accounting of other states. These differences create significant obstacles to doing business and prevent the implementation of accounting in the system of integrated business structures. The necessity of bringing state accounting and the basic principles of its construction with international standards is substantiated. This is necessary for the correct implementation of business integration structures in the system in order to ensure its effective functioning and obtain significant competitive advantages in the modern market environment. Changes in accounting should entail changes in tax and civil law, since the transition of Ukrainian accounting to international standards will become an important link in the integration of the Ukrainian economy into European and world economy. To justify the need to bring state accounting and the basic principles of its construction with international standards, the author proposed the following steps to solve this problem: – bringing into compliance the Provision (standard) of accounting of Ukraine with the International standards of financial reporting and accounting of other states; – ensuring adequate interpretation and compliance with the provisions of the Provision (standard) of accounting in Ukraine; – obtaining an audit opinion on the compliance of financial statements with the requirements of International Financial Reporting and Accounting Standards of other states.